Social Economy and Digital Mapping of Subak Sembung Ecotourism - Gede Mekse Korri Arisena; Anak Agung Keswari Krisnandika; Dwi Putra Darmawan (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2020)
The social, cultural, economic, and environmental potentials in Subak Sembung are not well-developed, such that these potentials have not been adequately explored by the local community. This study aimed to describe the synergy between subak and the ecotourism in supporting the sustainable national food stability program. Subak Sembung selected as the study location because its location in the middle of Denpasar City and already developed as ecotourism sites. There were 66 participants involved in this study. Formal surveys, rapid appraisal, and map-making through satellite imaging from the Google Earth Pro (GE) application were used to collect the data. Result revealed that the social economy social activities conducted by the farmer were: (1) seed-producing tools, fertilizers, pesticides, agricultural tools, (2) land-tillage, nurseries, cultivating, preserving the plant, harvesting, (3) marketing, and (4) the correlation between farmers, subak and ecotourism; worth to be developed as a tourist attraction site.